Analysis of Flexible Financial Management of Innovative Enterprises under the Background of Environmental Uncertainty - Wang, Yixuan (International Journal of Global Economics and Management, 2024)
Financial flexibility means that enterprises can offset their business risks through scientific fund management when facing the impact of uncertain risks. In recent years, due to the uncertainty of the external macro environment, international trade conflicts and corporate financing constraints, it is more difficult for enterprises to obtain resources from the outside, which puts higher requirements on the daily financial management of enterprises. More and more enterprises realize that cash flow plays an important role in mitigating risks and maintaining operation, which requires active financial flexible management. By combing the relevant literature at home and abroad, this paper systematically analyzes the concept and composition of the flexible financial management of enterprises, describes the existing problems in the flexible management of innovative enterprises, and puts forward the corresponding solutions.